(untitled) (Hekima Review, 2005)
In his Apostolic Letter Mane nobiscum Domine, Pope John Paul II declared October 2004 - October 2005 the year of the Eucharist. This mystery has been celebrated and understood in different ways. Our celebration of the Eucharist today needs a new understanding in order to reconcile our spiritual hunger with the material one, and to express, in a concrete way, our Christian faith. Thus, the celebration of the Eucharist should be life-oriented and context sensitive. In other words, our celebration should find an echo in people’s lives. We cannot fully celebrate this mystery of our Christian faith while there are many people, mostly in the third world countries, who do not have access to adequate food. If our celebration does not open our eyes and awaken our sensitivity to the needs of our sisters and brothers, then it becomes meaningless.